Calorie reformulation: a systematic review and meta-analysis examining the effect of manipulating food energy density on daily energy intake - Eric Robinson; Mercedes Khuttan; India McFarland-Lesser; Zina Patel; Andrew Jones (International Journal of Behavioral Nutrition and Physical Activity, 2022)
Abstract Background Dietary energy density is thought to be a contributor to obesity, but the extent to which different magnitudes and types of reductions to food energy density decreases daily energy intake is unclear. The primary objective was to systematically review and meta-analyse experimental studies that have examined the effect that manipulating energy density of food has on total daily energy intake. Secondary objectives were to examine moderators of the effect that altering energy density has on daily energy intake and effects on body weight. Methods A systematic review and multi-level meta-analysis of studies on human participants that used an experimental design to manipulate the energy density of foods served and measured energy intake for a minimum of 1 day. Results Thirty-one eligible studies sampling both children (n = 4) and adults (n = 27) contributed 90 effects comparing the effect of higher vs. lower energy density of served food on daily energy intake to the primary meta-analysis. Lower energy density of food was associated with a large decrease in daily energy intake (SMD = − 1.002 [95% CI: − 0.745 to − 1.266]). Findings were consistent across studies that did vs. did not manipulate macronutrient content to vary energy density. The relation between decreasing energy density and daily energy intake tended to be strong and linear, whereby compensation for decreases to energy density of foods (i.e. by eating more at other meals) was minimal. Meta-analysis of (n = 5) studies indicated that serving lower energy dense food tended to be associated with greater weight loss than serving higher energy dense food, but this difference was not significant (− 0.7 kg difference in weight change, 95% CIs: − 1.34, 0.04). Conclusions Decreasing the energy density of food can substantially reduce daily energy intake and may therefore be an effective public health approach to reducing population level energy intake. Trial registration Registered on PROSPERO ( CRD42020223973 ).